The active migration of Drosophila primordial germ cells. - Jaglarz, M.K.; Howard, K.R. (Development, 1995)
We describe our analysis of primordial germ cell migration in Drosophila wild-type and mutant embryos using high resolution microscopy and primary culture in vitro. During migratory events the germ cells form transient interactions with each other and surrounding somatic cells. Both in vivo and in vitro they extend pseudopodia and the accompanying changes in the cytoskeleton suggest that actin polymerization drives these movements. These cellular events occur from the end of the blastoderm stage and are regulated by environmental cues. We show that the vital transepithelial migration allowing exit from the gut primordium and passage into the interior of the embryo is facilitated by changes in the structure of this epithelium. Migrating germ cells extend processes in different directions. This phenomenon also occurs in primary culture where the cells move in an unoriented fashion at substratum concentration-dependent rates. In vivo this migration is oriented leading germ cells to the gonadal mesoderm. We suggest that this guidance involves stabilization of states of an intrinsic cellular oscillator resulting in cell polarization and oriented movement.